A measurement of affluence and poverty interdependence across countries: Evidence from the application of tail copula. (17th February 2020) - Matkovskyy, Roman
Abstract: This paper examines affluence and poverty interdependence across 185 countries and its evolution over 1969–2014. To estimate affluence and poverty interdependence and derive tail interdependences the tail copulae are applied to multivariate density function. The tail coefficients are estimated in the non‐parametric way as in Schmidt and Stadtmüller (2006). The estimates show, that poverty is less interdependent and continue to decrease, while affluence has asymptotically high global dependence, meaning a higher global dependence on and sensitivity to the well‐being of the affluent countries. The received results derive the pattern of the extreme interdependence and can help to identify poverty and affluence spill‐over across countries and regions and calculate the average sensitivity of a country to these phenomena on the global level and can potentially help in poverty reduction strategies within the Sustainable Development Goal by the United Nations.